ENERGY STORAGE (PENYIMPAN ENERGI) PADA BATERAI DENGAN APLIKASI SEPEDA (MOTOR) LISTRIK - R. Kurniawan Dwi S; m Ulinnuha (Cahaya Bagaskara : Jurnal Ilmiah Teknik Elektronika, 2020)
Forms of energy both potential energy ( eg Chemical , gravitational , electrical energy , temperature difference , solar thermal , etc. ) or kinetic energy (ie momentum ) . Some technologies only provide short-term energy storage , while others can be quite long as the power of using hydrogen or methane gas and hot or cold storage in the aquifer or bedrock. An initial solution to the problem of storing energy for electrical purposes was the development of electrochemical batteries as a storage device . Previously had limited battery used in electric power systems due to the relatively small capacity and high costs . However , since around the middle of the first decade of the 21st century , has developed a new battery technology that can now provide a certain scale for load - leveling capability significantly. Examples of electrical energy storage is a dry battery . Actually a lot of applications , for example that there are around us such as mobile phones , laptops , electric bikes , and others. The blow-back is a bike (motor ) power , as one of the efforts to reduce global warming and fossil energy savings